Community‐acquired Pseudomonas aeruginosa pneumonia manifested by bloody pleural effusion in a previously healthy infant: A case report. Issue 6 (13th May 2022) - Dong, Chunjuan; Shen, Fangfang; Dong, Hanquan; Dong, Lili; Fu, Ya; Xu, Yongsheng; Ning, Jing
Abstract: Background: Community‐acquired Pseudomonas aeruginosa pneumonia in immunocompetent children is a rare occurrence. Methods: A retrospective analysis of the clinical manifestations, imaging characteristics, laboratory examinations, and treatment of a child with community‐acquired Pseudomonas aeruginosa pneumonia presented with bloody pleural effusion. Results: The 1‐year‐old previously healthy patient, who developed community‐acquired pneumonia caused by Pseudomonas aeruginosa and influenza virus. The patient manifested bloody pleural effusion although his condition improved after anti‐infective therapy and closed thoracic drainage. After 10 days of hospitalization, his symptoms worsened, accompanied by hemoptysis, and the pathogen developed resistance to carbapenems. The antibiotic strategy was adjusted to combined antipseudomonal regimen. He developed low‐grade fever and was extubated, although these manifestations and imaging were eventually alleviated. Conclusions: Community‐acquired Pseudomonas aeruginosa pneumonia in children may be non‐septic, with bloody pleural effusion as presentation, and the disease may progress after 10 days of treatment due to drug resistance in Pseudomonas aeruginosa . Early extubation should be considered after adequate drainage. Abstract : A: Presence of pneumonia with pleural effusion on chest radiograph. B: Consolidation in the middle and lower lobes of the right lung accompanied by pleural effusion on chest CT. C: Thick‐walled cavities on chest CT. D: Chest radiograph after extubation